ChemInform Abstract: Divergent Synthesis of 4, 6‐Diarylated Pyridin‐2(1H)‐ones from Chalcones: Novel Access to 2, 4, 6‐Triaryl Pyridines. Issue 37 (September 2015) - Khajuria, Rajni; Kannaboina, Prakash; Kapoor, Kamal K.; Gupta, Annah; Raina, Gaurav; Jassal, Amanpreet Kaur; Rana, Love Karan; Hundal, Maninder S.; Das, Parthasarathi
Abstract Three component condensation of 1, 3‐diaryl‐2‐propen‐1‐ones with ethyl nitroacetate and ammonium acetate provides a convenient synthesis of 4, 6‐diarylated pyridin‐2(1H)‐ones.